Variations in Seawater pCO2 Associated With Vertical Mixing During Tropical Cyclone Season in the Northwestern Subtropical Pacific Ocean - Ko, Young Ho; Park, Geun-Ha; Kim, Dongseon; Kim, Tae-Wook (Frontiers in Marine Science, 2021)
This study examines interannual variations in the seawater CO2 partial pressure (pCO2) for months (August–October) with frequent tropical cyclone (TC) events in the northwestern subtropical Pacific Ocean (22°N–28°N, 135°E–145°E) between 2007 and 2017. The temperature-normalized pCO2 (pCO2nt) averaged over August–October showed a year-to-year variation ranging from 346–359 μatm over the 11 study years, which appeared to be related to the variation in vertical mixing that likely results from the TC activity in these months. Sea surface temperature and wind data consistently supported the association between mixing and TC intensity. Nonetheless, the pCO2 reduction caused by negative sea-surface temperature anomalies found over the TC season (July–October) shifted the study area from a CO2 source to a CO2 sink over these months. In the south (17°N–22°N) of the study area, mixing-driven variations in pCO2 were smaller during the same months, which appeared to be caused by the relatively deeper mixed layer depth and the more homogenous profile of CO2 in this tropical region. These results suggest that more extensive pCO2 measurements are required to fully resolve the effect of TCs on the carbonate system from the regional- to the basin-scale in the western Pacific Ocean, where TC intensity is expected to increase in the future.